Inequality and Poverty Impacts of Trade Distortions in Mozambique - Arndt, Channing; Thurlow, James (World Bank, Washington, DC, 2017)
Although Mozambique has considerable agricultural potential, rural poverty remains extremely high. This paper examines the extent to which global and domestic price distortions affect agricultural production and national poverty. The author develops a computable general equilibrium (CGE) and micro-simulation model of Mozambique that is linked to the results of a global model. This framework is used to examine the effects of eliminating global and national price distortions. Model results indicate that agriculture is adversely affected by current trade distortions due to policies in the rest of the world. While a removal of all merchandise trade distortions will reduce import prices, it will also raise agricultural production and reduce poverty. By contrast, removing only agricultural price distortions abroad will have little effect on Mozambique's agricultural sector. Model results indicate that Mozambique's own distortions are also biased against agriculture, with producers of processed agricultural products enjoying high protection levels. Removing these distortions causes a significant expansion of agricultural Gross Domestic Product (GDP) and a reduction in both poverty and inequality. The findings therefore suggest that removing own-country and rest-of-world distortions will have positive implications for agriculture and for the overall economy in Mozambique, and in particular it will reduce its poverty and inequality.